Reformasi : The struggle for Power in Post-Soeharto Indonesia - O'Rourke, Kevin (Allen & Unwin, 2002)
In July 1996, president Soeharto crossed a point of no return. small but vocal student groups were staging daily demonstrations to demand 'reformasi' indonesia's bywords for democratic reform.